Assessment of general bullying and bullying due to appearance of teeth in a sample of 11-16 year-old Peruvian schoolchildren. - Mayra Bazán-Serrano; Marcos J. Carruitero (Universidad de Concepción., 2017)
Abstract: Objective: To assess the incidence of general bullying and bullying due to the appearance of teeth in a sample of 11-16 year-old Peruvian schoolchildren. Materials and methods: Cross-sectional study with a sample of 218 students aged 11 to 16 years old (13.41±1.44), 109 males, and 153 from a public school. A survey on general bullying and the appearance of teeth was applied using a validated questionnaire. Results: The frequency of general bullying was 32.57%, and bullying due to dental appearance was 18.81%. General bullying (p=0.005) and dental appearance (p=0.024) were more frequent in the public school, but there were no statistically significant differences according to sex. The highest frequency of general bullying was related to name-calling, which accounted for 47.71%. Victimization by appearance of teeth in one or two occasions in the last two months accounted for 12.39%, according to participating subjects. Conclusion: General and tooth-related bullying was more frequent among students in public schools, with no significant differences according to sex.